ANALYSIS OF ILOCUTIONAL AND PERLOCUTIONAL ACTS IN THE REPUBLIC OF INDONESIA MINISTER OF HEALTH CONPRESSION REGARDING THE COVID-19 VACCINES ON THE MINISTRY OF HEALTH'S YOUTUBE CHANNEL - Diah Ayu Andini; Ayuk Setyaningrum; Asep Purwo Yudi Utomo (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Speech act means an activity which is done by humans through communication tools. Where speech acts are divided into 3 namely locutionary, illocutionary, and perlocutionary. In this article, we only discuss illocutionary and perlocutionary speech acts contained in the Indonesian Minister of Health's Presidential Decree on the Covid-19 Vaccine on the Ministry of Health's YouTube channel. An illocutionary speech act means a speech act that is not convoluted or can be said to be a frank speech act. Meanwhile, perlocutionary speech act means a speech act that has an impact on the speech partner. The use of the method in this article is in the form of the observe and note method, where the data obtained is analyzed using the causality method. In the analysis, the results obtained from the illocutionary analysis amounted to 8 from the 4 categories of illocutionary speech acts. The elaboration can include assertive illocutionary speech acts ('telling' obtained 2 data and 'state' obtained 1 data), directive illocutionary speech acts ('ordered' obtained 1 data and 'begged' obtained 1 data), commissive illocutionary speech acts (' promise' obtained 1 data), expressive speech acts ('thanking' obtained 1 data and 'praise' obtained 1 data). Meanwhile, the results obtained from perlocutionary analysis amounted to 7 from category 5 perlocutionary speech acts, the elaboration of which included 'reporting' speech obtained 2 data, 'scare' speech obtained 2 data, 'relief' speech obtained 1 data, 'fun' speech obtained 1 data , and the utterance 'request' obtained 1 data. In this research, it provides a benefit, namely providing additional knowledge and insight for the reader in the field of pragmatic studies in the form of illocutionary and perlocutionary speech acts.